Radiative Processes in Relativistic Outflows - Mastichiadis, Apostolos (2002)
1. Introduction 2. Superlumminal Motion 3. Doppler Boosting 4. Photon-Photon Pair Binding 5. Synchrotron Radiation 6. Inverse Compton Scattering 6.1. Thomson Scattering 6.2. Klein-Nishina Limit 7. Synchro Self-Compton Radiation 8. Continuity Equation 9. Coda References